2020
DOI: 10.1101/2020.08.24.265124
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertebrate features revealed in the rudimentary eye of the Pacific hagfish (Eptatretus stoutii)

Abstract: SUMMARYHagfish eyes are markedly basic compared to the eyes of other vertebrates, lacking a pigmented epithelium, a lens, and a retinal architecture built of three cell layers – the photoreceptors, interneurons & ganglion cells. Concomitant with hagfish belonging to the earliest-branching vertebrate group (the jawless Agnathans), this lack of derived characters has prompted competing interpretations that hagfish eyes represent either a transitional form in the early evolution of vertebrate vision, or a reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The amphioxus eye - with its inverted interpreted retina - does not fit directly into the stalk eye hypothesis, unlike the more advanced, bulging eyes of Conodonts (Donoghue, Forey, & Aldridge, 2000). The eye of the Hagfish may represent phase 3 (Figure 2) because it comprises an inverted retina around a vitreous spherical body but has no screening pigment layer (Dong & Allison, 2021). Next, the eye was retracted into the body without maintaining the optic stalk.…”
Section: Discussionmentioning
confidence: 99%
“…The amphioxus eye - with its inverted interpreted retina - does not fit directly into the stalk eye hypothesis, unlike the more advanced, bulging eyes of Conodonts (Donoghue, Forey, & Aldridge, 2000). The eye of the Hagfish may represent phase 3 (Figure 2) because it comprises an inverted retina around a vitreous spherical body but has no screening pigment layer (Dong & Allison, 2021). Next, the eye was retracted into the body without maintaining the optic stalk.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of transcripts are reported in Supplemental file 'eSupp_Transcript_ sequence_ID', and the RNA-Seq data are available from the Dryad Digital Repository: https://doi.org/10.5061/dryad. 79cnp5ht7 [55].…”
Section: Methods (A) Animal Ethics and Tissue Collectionmentioning
confidence: 99%
“…In addition, they have many cyclostome-specific features (e.g., lingual apparatus, velum, and mucous cartilage) not found in jawed vertebrates (Janvier, 1996;Oisi et al, 2013), and whether these features are inherited from the common ancestors of vertebrates or are synapomorphies of cyclostomes remains controversial (Yokoyama et al, 2021; also see Sugahara, 2021). The morphology of the hagfishes is regarded to be highly derived, including the degeneration of eyes because of adaptation to the deep sea (Gabbott et al, 2016;Dong & Allison, 2021), and many studies have instead used lampreys as a model for cyclostomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have many cyclostome-specific features (e.g., lingual apparatus, velum, and mucous cartilage) not found in jawed vertebrates (Janvier, 1996; Oisi et al, 2013), and whether these features are inherited from the common ancestors of vertebrates or are synapomorphies of cyclostomes remains controversial (Yokoyama et al, 2021; also see Sugahara, 2021). The morphology of the hagfishes is regarded to be highly derived, including the degeneration of eyes because of adaptation to the deep sea (Gabbott et al, 2016; Dong & Allison, 2021), and many studies have instead used lampreys as a model for cyclostomes. However, recent studies have suggested that some lamprey characteristics that had been regarded as ancestral to the cyclostomes, such as the larval-type oral apparatus (Miyashita et al, 2021) and the transformation of the larval endostyle into the thyroid after metamorphosis (Takagi et al, 2022), are in fact the derived state from the acquisition of the ammocoete larval stage.…”
Section: Introductionmentioning
confidence: 99%